2018
DOI: 10.1111/febs.14715
|View full text |Cite
|
Sign up to set email alerts
|

The inner ear proteome of fish

Abstract: The mechanisms that underpin the formation, growth and composition of otoliths, the biomineralized stones in the inner ear of fish, are largely unknown, as only a few fish inner ear proteins have been reported. Using a partial transcriptome for the inner ear of black bream (Acanthopagrus butcheri), in conjunction with proteomic data, we discovered hundreds of previously unknown proteins in the otolith. This allowed us to develop hypotheses to explain the mechanisms of inorganic material supply and daily format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 79 publications
(129 reference statements)
3
47
0
Order By: Relevance
“…While we show here that we can successfully sequence several known modern skeletal proteins in fossil coral specimens, future method refinement may consider inclusion of other, non-enzymatic, peptide cleavage methods; this could include the use of cyanogen bromide (e.g. 73 ), although significant accumulation of methionine oxidation in fossil specimens would minimize its effectiveness 74 .…”
Section: Discussionmentioning
confidence: 96%
“…While we show here that we can successfully sequence several known modern skeletal proteins in fossil coral specimens, future method refinement may consider inclusion of other, non-enzymatic, peptide cleavage methods; this could include the use of cyanogen bromide (e.g. 73 ), although significant accumulation of methionine oxidation in fossil specimens would minimize its effectiveness 74 .…”
Section: Discussionmentioning
confidence: 96%
“…The absence of pks1 does not visibly appear to affect hair cell development that are required for otolith nucleation either [ 9 ]. It has been previously suggested that apolipoprotein could potentially bind polyketide synthase [ 4 , 25 ]. Given our RNA-seq analysis of nco , we see no significant change in any apolipoprotein expression.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are all part of a regulatory network during hypergravity-mediated bone formation [ 52 ]. Furthermore, the presence of osteoblast-associated proteins within teleost otoliths suggest a common mechanism between bone mineralization and otolith biomineralization [ 4 ]. Future studies will attempt to clarify the roles of Endothelin-1 and eNOS signaling pathways during biomineralization events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a lot of proteins involved in the biomineralization of calcium phosphate and calcium carbonate are IDPs . These include, for example, mammalian proteins: osteopontin (OPN), bone sialoprotein (BSP), dentin sialophosphoprotein (DSPP), as well as a zebrafish otolith matrix protein Starmaker (Stm), and its homologs from other fish species . However, more ordered proteins are also involved, for example: otoconin‐90 (OC90), amorphous calcium carbonate‐binding protein (ACCBP), otolin‐1 …”
Section: Introductionmentioning
confidence: 99%